2008
DOI: 10.1007/s10257-008-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory classification of applications in the realm of collaborative modeling and design

Abstract: The high complexity and diversity of today's design projects demands the participation of multiple experts. The participating experts can influence the design process by sharing their perspective, expertise and resources. The involvement of various experts is often known as collaborative modeling and design. A collaborative modeling environment can encompass various geographical or organizational boundaries. In this paper, we provide a classification to study various aspects of this important issue through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Our intention is to help the domain analysts maintain high quality standards in their work by reducing the mental burden that they have to carry during the modeling process; • Collaboration: Large domains often cross multiple disciplines and require different domain experts to effectively communicate with each other during the domain modeling process. Previous research has shown that ad-hoc collaboration strategies can lead to inconsistent models (Bagheri and Ghorbani 2010); hence, our goal is to provide a platform that supports for easy and effective collaboration between the domain analysts; • Knowledge Transfer: Software product lines are often designed for the purpose of being used during long periods of time and for multiple generations of software applications; therefore, it is likely that the original domain analysts will no longer be available at a later stage of a project to explain and justify their modeling decisions. For this reason, the decision support platform needs to unambiguously capture the decisions of the domain modelers and efficiently document them for future reference; • Traceability: As a domain evolves, the documents that were used earlier during the domain modeling process may gradually become obsolete.…”
Section: Introductionmentioning
confidence: 99%
“…Our intention is to help the domain analysts maintain high quality standards in their work by reducing the mental burden that they have to carry during the modeling process; • Collaboration: Large domains often cross multiple disciplines and require different domain experts to effectively communicate with each other during the domain modeling process. Previous research has shown that ad-hoc collaboration strategies can lead to inconsistent models (Bagheri and Ghorbani 2010); hence, our goal is to provide a platform that supports for easy and effective collaboration between the domain analysts; • Knowledge Transfer: Software product lines are often designed for the purpose of being used during long periods of time and for multiple generations of software applications; therefore, it is likely that the original domain analysts will no longer be available at a later stage of a project to explain and justify their modeling decisions. For this reason, the decision support platform needs to unambiguously capture the decisions of the domain modelers and efficiently document them for future reference; • Traceability: As a domain evolves, the documents that were used earlier during the domain modeling process may gradually become obsolete.…”
Section: Introductionmentioning
confidence: 99%